PENGABDIAN MASYARAKAT PADA KOMUNITAS ANAK STUNTING : GIZI SEIMBANG ANAK BALITA DI KELURAHAN CIBEBER - Rahayu Savitri; Afrieani Deasy; Enok Sobariah; Briefman Tampubolon; Moch Rezha Alfiqri; Asep Miftah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Stunting is a growth failure problem in children due to chronic malnutrition, which results in delayed physical and cognitive development and reduced productivity in the future. Cibeber Village has been identified as an area at risk of stunting, triggered by parents' limited knowledge regarding balanced nutritional composition and inappropriate feeding patterns. This community service activity aims to improve parents' knowledge and skills in stunting prevention through balanced nutrition education. The methods used include interactive counseling, discussions, the use of leaflets and booklets, and demonstrations of simple supplementary feeding (PMT). Evaluation was carried out by comparing pre-test and post-test scores. The results of the activity showed a significant increase in participants' knowledge regarding balanced nutrition and positive behavioral changes in toddler feeding patterns. Through the role of universities in providing scientific education and community empowerment, this strategy has proven effective in supporting stunting prevention efforts at the community level in a structured and sustainable manner.